PENGARUH PENGGUNAAN KARTU HURUF BERGAMBAR UNTUK MENGATASI KESULITAN MEMBACA KATA PADA SISWA KELAS 1 SDN 007 LONG MESANGAT - Jamiatul Aini; Agnes Berra; Azamul Fadly Noor Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Difficulty in reading among lower-grade elementary school students is a real challenge that requires innovative learning media. This study aims to improve students' reading skills at SDN 007 Long Mesangat by utilizing illustrated letter cards. The method used was Classroom Action Research (CAR), conducted in two cycles. The research subjects were first-grade students identified as having difficulties recognizing letters and spelling syllables. Data were collected through oral tests, observations, and documentation. The results showed a significant improvement in reading abilities. In the pre-cycle, classical completeness was only 30% (4 students). After the implementation of illustrated letter cards in Cycle I, completeness increased to 60% (8 students), and reached 90% (12 students) in Cycle II. The use of this media also enhanced students' learning motivation and engagement. In conclusion, the illustrated letter card media is highly effective in overcoming reading difficulties of students at SDN 007 Long Mesangat. This media successfully bridges abstract concepts with concrete visuals, making the learning process more interactive and student-centered.